52 suburbs - Hawson, Louise ([Sydney, N.S.W.] : [Louise Hawson], 2009)
Louise Hawson's blog documenting her exploration of 52 Sydney suburbs over 14 months. The blog documents one suburb a week and contains photographs.The material is also going to be published as a book.
"A search for beauty in the Sydney 'burbs".
Title from home page (viewed on 24 January 2011).
Text and graphics.
Available via World Wide Web. On 24/01/11 freely available at: http://www.52suburbs.com
System requirements: Adobe Acrobat Reader to access files in a PDF format.
Selected for archiving
Keywords: Hawson, Louise -- Blogs; Suburban life -- New South Wales -- Sydney -- Blogs; Suburban life -- New South Wales -- Sydney -- Pictorial works; Suburbs -- New South Wales -- Sydney -- Blogs; Suburbs -- New South Wales -- Sydney -- Pictorial works; Sydney (N.S.W.) -- Blogs; Sydney (N.S.W.) -- Pictorial works